Features of standardization and registration of dietary supplements compared to drugs - Bevz, Olena; Kryvanych, Olga; Fedosov, Andrii; Sych, Irina; Perekhoda, Lina (ScienceRise: Pharmaceutical Science, 2019)
The constant increase in the number of dietary supplements and the demand for them, as well as the progression of self-medication with the use of over-the-counter medicines, raises questions about their effectiveness, safety and bioequivalence. There are also questions about the criteria for ingredients, production, standardization and registration of finished medicines and dietary supplements. The aim. The aim of the work is to summarize information on the features of standardization, certification and registration of dietary supplements in comparison with drugs in the territory of Ukraine. Materials and methods. Data were collected and analyzed from the current scientific literature and regulatory documents to perform the research. Results. Production, standardization and circulation of finished medicines and dietary supplements is carried out in accordance with the current legislation of Ukraine, international standards (ISO, ICH, GxP) and the requirements of the State Pharmacopoeia of Ukraine. According to these documents, the requirements for the quality of medicines and dietary supplements differ, but unlike ten years ago, today there can be increased regulation and control on the part of the state and law enforcement agencies to eliminate cases of falsification and circulation of unregistered means. The current legislation of Ukraine regulating the production, quality and circulation of finished medicines harmonized with the EU puts forward requirements for providing the population with quality imported / domestic medicines. Regarding dietary supplements, the procedure of harmonization of the legislation of Ukraine with the EU has started, which in the future should lead to improvement of the quality of these remedies and increase of control from the state. Discussion. We generalized requirements for the features of standardization and registration of dietary supplements in the territory of Ukraine, which must be observed in the manufacture, quality control, registration and sale of dietary supplements. Conclusions. Simpler registration, implementation and wider market conditions (multi-level marketing system, Internet) lead to a rapid increase in the production of dietary supplements in Ukraine and their imports. We generalized information about the requirements for the quality of dietary supplements in comparison with finished medicines, and the features of their registration in the territory of Ukraine according to the current legislation